Cultural criminology and the carnival of crime - Presdee, Mike, 1944- (Routledge, 2000)
Cultural Criminology and the Carnival of Crime attempts to make sense of the current increase in violence, cruelty, hate and humiliation, which has come to permeate daily life. The text argues that an overly organised economic world has provoked a widespread desire for extreme, oppositional forms of popular and personal pleasure. This desire has resulted in a cathartic 'second life' of illicit pleasures often deemed criminal by those in power. Amongst the exciting issues Mike Presdee addresses are:* joyriding* street crime* antisocial behaviour in private via the inter.